1992
DOI: 10.1002/mds.870070210
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid antibodies to coronavirus in patients with Parkinson's disease

Abstract: The etiology of Parkinson's disease remains unknown, and a search for environmental agents continues. In 1985, Fishman induced infection of the basal ganglia by a coronavirus in mice. Although coronavirus is recognized primarily as a respiratory pathogen in humans, its affinity for the basal ganglia led us to investigate its possible role in human Parkinson's disease. The cerebrospinal fluid of normal controls (CTL) (n = 18), and patients with Parkinson's disease (PD (n = 20) and other neurological disease (ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(171 citation statements)
references
References 21 publications
3
164
0
4
Order By: Relevance
“…Overall, however, there is no clear evidence for involvement of an infectious agent in PD. Case-control studies have analyzed antibody titres in serum or cerebrospinal fluid for a large number of viruses (including influenza), as well as Bordetella pertussis [146,[534][535][536][537][538][539]. Whilst most studies found similar antibody levels in cases and controls, one study observed higher antibody levels for herpes simplex [538], while another study found lower antibody levels for herpes simplex, rubella and measles [539].…”
Section: Infectionsmentioning
confidence: 99%
“…Overall, however, there is no clear evidence for involvement of an infectious agent in PD. Case-control studies have analyzed antibody titres in serum or cerebrospinal fluid for a large number of viruses (including influenza), as well as Bordetella pertussis [146,[534][535][536][537][538][539]. Whilst most studies found similar antibody levels in cases and controls, one study observed higher antibody levels for herpes simplex [538], while another study found lower antibody levels for herpes simplex, rubella and measles [539].…”
Section: Infectionsmentioning
confidence: 99%
“…118,119 In humans, spirochetes have been found in Lewy bodies of PD patients. 29 Other infections, such as viral encephalitis, 120 AIDS-associated opportunistic infections of the basal ganglia, 121 coronavirus, 122 and other infections, 63,123,124 have been found in PD and could be important in stimulating inflammation and autoimmune responses. Richy and Mégraud 125 have stressed, however, that more rigorous investigations will be required to establish whether a causal link exists between infections and PD.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…This epidemic gave rise to the belief that PD might be associated with an infectious agent such as a virus, especially Epstein Barr virus, influenza virus, coronavirus and Japanese encephalitis virus (7)(8)(9)(10)(11)(12). Since the 1980's, several additional microorganisms such as Borrelia burgdorferi, Haemophilus influenzae, Corynebacterium diphtheriae, Cryptococcus neoformans, Mycoplasma pneumoniae and Helicobacter pylori (13)(14)(15)(16) have been postulated as agents that could be associated etiologically with PD or another kind of parkinsonism.…”
Section: Introductionmentioning
confidence: 99%